ECONOMIC ANALYSES, INJURY LEVELS AND THRESHOLDS FOR EFFECTIVE MANAGEMENT OF EARIAS VITTELLA (FAB.) ON GOSSYPIUM HIRSUTUM - M. T. Jan; S. A. Shad; C. Karavina; M. Ahmad; M. A. Saleem; M. Binyameen (Journal of Animal and Plant Sciences, 2020)
Spotted bollworm, Earias vittella Fab. (Lepidoptera: Noctuidae), is a serious insect pest of cotton that reduces crop yield and deteriorates lint quality. Field experiments were conducted at the Central Cotton Research Institute, Multan, Pakistan for two consecutive years (2009 and 2010) to estimate economic injury level (EIL) and economic threshold level (ETL). For economic analyses, gain threshold (GT) and benefit-cost ratio (BCR) were assessed by spraying cypermethrin, deltamethrin and spinosad at four thresholds levels (0, 3, 5 and 7% damage) and compared with unsprayed treatment (control) for a long and a short duration cotton genotype. The numbers of damaged fruits were almost similar while larval populations and the numbers of healthy fruits were different between the two genotypes. Insecticides applications at selected percent damage levels kept E. vittella larval infestation and bolls damage well below from the total fruit losses of 60-74% in unsprayed treatment. Increase in percent damage levels decreased the cost of protection (CP) and the net monetary profit (NMP). ETL for long duration genotype (CIM-496) is suggested at 5% damage level with a larval population of 1.12-1.22 larvae per 25 plants (GT basis) and 4.5 larvae per 25 plants (BCR basis). For short duration genotype (CIM-506), ETL at 3% damage level with larval population of 1.4-1.33 larvae per 25 plants and 3.3 to 3.9 larvae per 25 plants on GT and BCR basis, respectively is recommended. Timely application of insecticides at ETLs is suggested as economical mean for an effective control of E. vittella on cotton crop.
Keywords: Cotton; ETL; larval population; pest management; gain threshold; benefit-cost ratio